2006
DOI: 10.2169/internalmedicine.45.1752
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-Associated Prostatitis Complicating Autoimmune Pancreatitis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(64 citation statements)
references
References 13 publications
0
61
1
2
Order By: Relevance
“…We found that biopsy was mandatory for confirming abundant IgG4-positive plasma cells and lymphocyte infiltration; in addition, a favorable response to corticosteroid therapy was helpful in identifying AIP. To date, a few AIP-associated prostate lesions have been reported, but detailed image findings have not been previously described [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…We found that biopsy was mandatory for confirming abundant IgG4-positive plasma cells and lymphocyte infiltration; in addition, a favorable response to corticosteroid therapy was helpful in identifying AIP. To date, a few AIP-associated prostate lesions have been reported, but detailed image findings have not been previously described [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…It disappears shortly after starting steroid treatment (b) retroperitoneal fibrosis [68], tubulointerstitial nephritis [69,70] and interstitial pneumonitis [71,72]. Other lesions reported include hypophysitis [73], chronic thyroiditis [54], pseudotumor of the liver [74,75], gastric ulcer [76], prostitis [77], Schönlein-Henoch purpura and autoimmune thrombocytopenia [78]. It is unknown whether all of them are real complications of AIP.…”
Section: Extrapancreatic Organ Involvementmentioning
confidence: 99%
“…Many authors have reported extra-pancreatic lesions associated with AIP, such as lachrymal and salivary [22,64], lung [26,27,[65][66][67][68], mediastinal [25], bile duct [8,28,69], renal [34,35,70,71], retroperitoneal [12] and prostatic [36][37][38] lesions. Recently, the concept of 'IgG4-related diseases' has been proposed because pathological findings similar to those of pancreatic lesion, more specifically infiltration of IgG4-bearing plasma cells, lymphocyte and fibrosis, were found in these extra-pancreatic lesions [2,12,22,33,[39][40][41][42].…”
Section: Extra-pancreatic Lesions Associated With Aip and Igg4-relatementioning
confidence: 99%
“…In addition, a variety of extra-pancreatic lesions, such as lachrymal and salivary gland lesions [22][23][24], hilar lymphadenopathy [24,25], interstitial pneumonia [24,26,27], sclerosing cholangitis [2,8,24,[28][29][30], retroperitoneal fibrosis [12,24,29,[31][32][33], renal lesions [24,34,35], and prostatic lesions [24,[36][37][38] have been reported to be complicated with AIP. Extra-pancreatic lesions show systemic distribution and share similar pathological and clinical findings with AIP, such as storiform fibrosis, prominent lymphoplasmacytic infiltration and abundant IgG4-bearing plasma cells [12,22,25,33], and have a favorable response to corticosteroid therapy [3, 4, 13-15, 22, 28-30].…”
Section: Introductionmentioning
confidence: 99%